AN INFORMATION SYSTEM OF PREDICTIVE MAINTENANCE ANALYTICAL SUPPORT OF INDUSTRIAL EQUIPMENT - Vlasov, Andrey I.; Echeistov, Vladimir V.; Krivoshein, Aleksey I.; Shakhnov, Vadim A.; Filin, Sergey S.; Migalin, Vladimir S. (Journal of Applied Engineering Science, 2018)
The work considers the stages of design and operation of the information expert system of predictive maintenance analytical support of industrial equipment exemplified by vacuum devices. Special attention was paid to the study of the methods of maintenance of the equipment and also to the development of a concept of a modern system of predictive maintenance. The formalization of the test system of predictive maintenance was performed in the package MS Excel using the programming language Visual Basic for Applications. The result of work is the development of an automated expert system of analysis of the methods and means of predictive maintenance of vacuum devices. The particular results were obtained with the support of the Ministry of Education and Science of the Russian Federation within the project of the Agreement No. 14.579.21.0142 UID RFMEFI57917X0142.